A Formação Contínua Docente Na Rede Pública Estadual Paulista: As Relações Entre O Professor Coordenador Do Núcleo Pedagógico, O Professor Coordenador E O Professor. - Matsuda, Adelina Braga [UNIFESP] (2018)
The Research Analyzes The Relationships Of Work In The Continuous Formation Of Teachers Between The Coordinating Teacher Of The Pedagogical Nucleus, The Coordinating Teacher And The Teacher Who Works In The Schools Of The State Of São Paulo. The Study On Continuing Teacher Education Sought Theoretical Support In The Contributions Of Marin (1995). Nóvoa (2009) Contributed From The Conceptualization Of Teacher Professionalization. An Overview Of The Political Composition Of The State Department Of Education Of São Paulo, In Its 23-Year Peer-District Mandate, Was Drawn From The Theoretical Contributions Of Russo & Carvalho (2012) And Sanfelice (2010); And To Analyze The Public Policy Propositions In The State Of São Paulo, We Turn To The Policy Cycle Approach Proposed By Ball (1992, 1998, 2001, 2008), Especially In What Concerns The Concept Of Bricolage. In Relation To School Cultures, Research Is Based On The Ideas Of Viñao Frago (2000, 2008). The Empirical Investigation Used Semi-Structured Interviews With 2 C